Genome-wide association study of nocturnal blood pressure dipping in hypertensive patients - Jenni M. Rimpelä; Ilkka H. Pörsti; Antti Jula; Terho Lehtimäki; Teemu J. Niiranen; Lasse Oikarinen; Kimmo Porthan; Antti Tikkakoski; Juha Virolainen; Kimmo K. Kontula; Timo P. Hiltunen (BMC, 2018)
Abstract Background Reduced nocturnal fall (non-dipping) of blood pressure (BP) is a predictor of cardiovascular target organ damage. No genome-wide association studies (GWAS) on BP dipping have been previously reported. Methods To study genetic variation affecting BP dipping, we conducted a GWAS in Genetics of Drug Responsiveness in Essential Hypertension (GENRES) cohort (n = 204) using the mean night-to-day BP ratio from up to four ambulatory BP recordings conducted on placebo. Associations with P < 1 × 10− 5 were further tested in two independent cohorts: Haemodynamics in Primary and Secondary Hypertension (DYNAMIC) (n = 183) and Dietary, Lifestyle and Genetic determinants of Obesity and Metabolic Syndrome (DILGOM) (n = 180). We also tested the genome-wide significant single nucleotide polymorphism (SNP) for association with left ventricular hypertrophy in GENRES. Results In GENRES GWAS, rs4905794 near BCL11B achieved genome-wide significance (β = − 4.8%, P = 9.6 × 10− 9 for systolic and β = − 4.3%, P = 2.2 × 10− 6 for diastolic night-to-day BP ratio). Seven additional SNPs in five loci had P values < 1 × 10− 5. The association of rs4905794 did not significantly replicate, even though in DYNAMIC the effect was in the same direction (β = − 0.8%, P = 0.4 for systolic and β = − 1.6%, P = 0.13 for diastolic night-to-day BP ratio). In GENRES, the associations remained significant even during administration of four different antihypertensive drugs. In separate analysis in GENRES, rs4905794 was associated with echocardiographic left ventricular mass (β = − 7.6 g/m2, P = 0.02). Conclusions rs4905794 near BCL11B showed evidence for association with nocturnal BP dipping. It also associated with left ventricular mass in GENRES. Combined with earlier data, our results provide support to the idea that BCL11B could play a role in cardiovascular pathophysiology.